Voices of Diversity: How Language Mirrors Cultural Identity Across Communities in KH Abdul Chalim University - Faturrohman, Moch Zaky; Kusrini, Nurul Azizah Ria (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2024)
This study explores how students at KH Abdul Chalim University, a multiethnic institution in Indonesia, negotiate their linguistic identities in an environment where heritage languages, Indonesian, and global digital registers intersect. The research addresses the broader concern of heritage language decline in Indonesia, particularly among younger generations. It seeks to understand how language use reflects both cultural preservation and adaptation in academic and social contexts. Using a qualitative ethnographic design, data were collected through semi-structured interviews and participant observation with four students representing different ethnic backgrounds, including Javanese, Sundanese, Riau Malay, and Flores. Thematic analysis revealed three interrelated findings: first, a clear language domain shift, with heritage languages confined mainly to private and family spaces while Indonesian dominates public and academic interactions; second, heritage languages continue to function as symbolic markers of cultural identity but face the threat of reduced practical use, creating a growing tension between symbolic value and communicative function; and third, students actively construct hybrid identities by shifting between heritage languages, Indonesian, and digital vernaculars, with social media playing a dual role—accelerating the dominance of Indonesian while simultaneously offering opportunities for revitalizing local languages through creative content. The findings demonstrate that heritage languages remain emotionally significant but risk becoming increasingly symbolic unless deliberate efforts are made to sustain their everyday use. The study highlights the significance of educational and digital initiatives in preserving linguistic diversity, positioning universities and social media platforms as vital spaces for safeguarding Indonesia’s cultural and linguistic heritage.